Civic Participation and Governance in Sustainable Development Initiatives: Evidence from Indonesia - Mappasessu Mappasessu; Nabila Tijani Tharifah; Sunusi Dauda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines how institutionalized civic participation shapes governance performance and sustainability outcomes across Indonesian localities through an empirical mixed-methods design integrating survey modeling and qualitative inquiry. Quantitative findings demonstrate that participatory intensity predicts governance responsiveness, policy learning capacity, and sectoral sustainability performance, while qualitative evidence reveals that deliberative forums operate as adaptive interfaces connecting citizen knowledge with administrative decision-making. Cross-scalar coordination emerges as a central mechanism through which participation enhances procedural legitimacy, collective efficacy, and institutional trust, particularly when civil society mediation and digital engagement infrastructures expand inclusivity and accountability. Environmental initiatives illustrate how participatory practices embed sustainability norms into routine governance, producing iterative feedback loops that strengthen implementation resilience. Persistent structural constraints, including uneven institutional capacity and symbolic inclusion, moderate these gains and highlight the necessity of organizational reform. The study contributes a multi-layered analytical framework that conceptualizes participation as a governance technology capable of generating measurable sustainability dividends when supported by institutional coherence, digital competence, and civic learning, advancing theoretical and methodological debates on participatory sustainability governance.